Analysis of power quality of Jamun biodiesel operated CI engine using STATCOM - Arunkumar Munimathan; Silambarasan Rajendran; Vasanthi R; Vinayagam Mohanavel; P. Padmavathy; Manikandan Ayyar; Sathish Kannan; Manzoore Elahi M. Soudagar; S. Kaliappan (Results in Engineering)
The future of the global energy system depends on renewable and sustainable energy. Biodiesel is also used in stationary CI engines in institutions, drilling, mining, pharmaceutical, and healthcare activities. These stationary engines must provide high-quality power to protect the various pieces of equipment used in the above applications. Fuel type can affect CI engine power quality. An alternative fuel's power quality, torque, and vibration will determine its suitability for internal combustion engines in cars and stationary applications. Thus, this experiment measures the electrical performance of a stationary engine-generator (single cylinder, 5.2 kW) by applying a resistive load and measuring both the overall power and each phase's power. The CI engine has a STATCOM-based FACTS controller to improve power quality. The acoustic and vibrational effects of biodiesel and its blends on CI engines are also being studied. Throughout this investigation, the experimental engine is powered by a mixture of conventional diesel and jamun biodiesel in quantities of 20 %, 40 %, 60 %, 80 %, and 100 %. The results reveal that the B20 blend exhibited superior performance with a 10 % improvement in power quality compared to diesel. At 2400 RPM, the vibration level for B20 was the lowest at 16.8 m/s², compared to 17.32 m/s² for diesel, indicating smoother engine operation. Sound levels also decreased with B20 due to improved combustion efficiency. STATCOM effectively mitigated current harmonics and improved the power factor, enhancing power quality by regulating voltage and balancing loads. The study highlights that while higher blends like B100 showed reduced power and torque due to lower calorific value and higher viscosity, B20 provided an optimal balance of performance and environmental benefits. These findings demonstrate the potential of Jamun biodiesel as a sustainable alternative fuel and underscore the importance of STATCOM in addressing power quality challenges in biodiesel-powered systems.